(Un-)Interpretability in Expert Evidence: An Inquiry into the Frontiers of Evidential Assessment - Alex Biedermann; Kyriakos N. Kotsoglou (Quaestio Facti)
Evidence law regimes across several contemporary legal orders provide a host of doctrinal devices designed to probe various sorts and sources of information, especially with respect to their accuracy and reliability. These legal provisions, however, are vulnerable to or even tolerant towards uninterpretable evidence, that is evidence whose probative value cannot be assessed. This article critically examines and discusses the “littering paths” of uninterpretable evidence in legal proceedings. We point out the misinformative character and potentially misleading impact on criminal adjudication when using scientific evidence for purposes that, strictly speaking, the evidence cannot help with. We identify common causes and possible remedies and argue that to track uninterpretability, it is necessary to understand what exactly it means to say that a piece of evidence is probative in the procedural space of reasons, and how to draw the line between informative and non-informative items of evidence.